Sliding mode control of shape memory alloy actuated structure for vibration control. (2015) - Dhanalakshmi, K.; Umapathy, M.; Ezhilarasi, D.
This paper presents the design and experimental evaluation of sliding mode controller to minimise structural vibration of a cantilever beam using shape memory alloy (SMA) wires as control actuators and piezoceramics as sensor and disturbance actuator. Linear dynamic models of the smart cantilever beam are obtained using online recursive least square parameter estimation. A digital control system that consists of Simulink™ modelling software and dSPACE DS1104 controller board is used for identification and control. The effectiveness of the controller is shown through simulation and experimentation by exciting the structure at resonance.